A TREM1 variant alters the accumulation of Alzheimer‐related amyloid pathology. Issue 3 (March 2015) - Replogle, Joseph M.; Chan, Gail; White, Charles C.; Raj, Towfique; Winn, Phoebe A.; Evans, Denis A.; Sperling, Reisa A.; Chibnik, Lori B.; Bradshaw, Elizabeth M.; Schneider, Julie A.; Bennett, David A.; De Jager, Philip L.
<x xml:space="preserve">Abstract</x> Objective Genome‐wide association studies have linked variants in TREM2 (triggering receptor expressed on myeloid cells 2) and TREML2 with Alzheimer disease (AD) and AD endophenotypes. Here, we pursue a targeted analysis of the TREM locus in relation to cognitive decline and pathological features of AD. Methods Clinical, cognitive, and neuropathological phenotypes were collected in 3 prospective cohorts on aging (n = 3, 421 subjects). Our primary analysis was an association with neuritic plaque pathology. To functionally characterize the associated variants, we used flow cytometry to measure TREM1 expression on monocytes. Results We provide evidence that an intronic variant, rs6910730G, in TREM1, is associated with an increased burden of neuritic plaques (p = 3.7 × 10−4), diffuse plaques (p = 4.1 × 10−3), and Aβ density (p = 2.6 × 10−3) as well as an increased rate of cognitive decline (p = 5.3 × 10−3). A variant upstream of TREM2, rs7759295C, is independently associated with an increased tau tangle density (p = 4.9 × 10−4), an increased burden of neurofibrillary tangles (p = 9.1 × 10−3), and an increased rate of cognitive decline (p = 2.3 × 10−3). Finally, a cytometric analysis shows that the TREM1 rs6910730G allele is associated with decreased TREM1 expression on the surface of myeloid cells (p = 1.7 × 10−3). Interpretation We provide evidence that 2 common variants within the TREM locus are associated with pathological features of AD and aging‐related cognitive decline. Our evidence suggests that these variants are likely to be independent of known AD variants and that they may work through an alteration of myeloid cell function. Ann Neurol 2015;77:469–477